Researches of holocaust and national collective memory in Baltic region - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2002)
This was the title of the international scientific conference organised at Vytautas Magnus University on 17–18 May 2002. Organisers of the conference were the Faculty of Humanities, the Genocide Victims Rescue Research Centre, the Institute of Political Science and Diplomacy, and the Centre for European Studies. The Soviet regime, both in the pre–war Bialystok Voivodeship, in western Belarus, and in Lithuania (and, we might add, in Latvia and in the western Ukraine as well), extremely complicated the relationship of the mainstream ethnic community with the minorities, particularly the Jews. The Soviet years further emphasised national stereotypes and facilitated the motivation of the Holocaust: in recent years, the theory of two genocides has emerged and flourished, and, as we have seen, not only in Lithuania. This theory has become a feature of the lives of many people who lived through the Soviet era, however briefly.